MOTIF BANDRONG LISUNG PADA BATIK CIKADU DITINJAU DARI KAJIAN SEMANTIK INKUISITIF - Fauzi, Rizal; Saputra, Desma Yuliadi; Ma’arif, Minhatul; Khoiriyah, Eneng Liah (Universitas Sultan Ageng Tirtayasa, 2023)
This research adopts a qualitative descriptive design to explain and depict the characteristics of the Bandrong Lisung motif in Batik Cikadu. Using a descriptive approach, the research explores the meanings of the motif without strict limitations and employs qualitative methods to understand the visual language and meanings within the motif, focusing on the semantic script and cognitive aspects. The Bandrong Lisung motif in Batik Cikadu serves as a visualization of the gratitude of the Pandeglang community towards the rice harvesting activities. As a representation of rural life, this motif honors the role of agriculture in local culture, symbolizing gratitude for abundant harvests with profound spiritual and social significance.The analysis of movements in the Banderong Lesung Dance reveals symbolism in each gesture, creating a portrayal of rural life and expressing the cultural richness of agrarian society. Facial expressions and body movements provide emotional dimensions and cognitive language that connect the audience to everyday life. The aesthetic elements of the Banderong Lesung Dance, including color, motifs, and costumes, convey symbolic meanings associated with nature and agriculture. Accessories such as cloth and head ornaments play a crucial role in the semantic script, conveying deep cultural messages. The Banderong Lesung Dance creates a distinctive atmosphere through its musical style, rhythm, and tempo, enriching the audience's experience. The analysis of space and backgrounds highlights the importance of visual elements in the performance context, deepening the cultural meaning of the dance. As a local heritage, the Banderong Lesung Dance is not merely a dance but a form of preserving values and cultural identity. This analysis illustrates how the Pandeglang community preserves the authenticity of this dance as an inseparable part of their cultural heritage, making it more than just a performance art but a living legacy connecting them to their cultural roots.